ANALYSIS OF THE FINANCIAL PERFORMANCE OF ISLAMIC COMMERCIAL BANKS BASED ON THE ISLAMICITY PERFORMANCE INDEX METHOD FOR THE PERIOD 2018-2023 - Muhammad Wahyu Nurdin; Riskayanto Riskayanto; Siti Aisyah (Asosiasi Dosen Muda Indonesia, 2025)
The development of the sharia bank in Indonesia is making progress. The quantitative growth of Sharia banking has been demonstrated by the increasing number of sharia public banks and sharia units established. The study aims to analyze the measurement of the Islamicity Performance Index on the financial performance of the Shariah general bank projected by the Return on Asset (ROA) period 2018-2023. The population of this research was determined using purposive sampling and obtained 6 Sharia General Banks. Samples collected using the method of Purposive Sampling are as many as 6 Sharia General Bank selected. Data obtained in the Company`s Annual Report. The data analysis technique in this study uses double linear regression with the SPSS version 29 program. The results of the study showed that partially the variable Profit Sharing Ratio has no influence on Return on Asset, while Zakat Performance Ratio, Equitable Directors Employee Ratio, Director Employee Ratio, and Islamic Income Vs Non-Islamic Income Ratio have no effect on the Return on Asset. Simultaneosly, variables such as Profit Sharing Ratio, Zakat Performance Ratio, and Equitable Distribution Ratio have influenced the return on asset.